2014
DOI: 10.1063/1.4896558
|View full text |Cite
|
Sign up to set email alerts
|

Formation of unique trimer of nitric oxide on Cu(111)

Abstract: We report that NO molecules unexpectedly prefer a trimeric configuration on Cu(111). We used scanning tunneling microscopy (STM) at 6 K, and confirmed that the NO molecule is bonded to the face-centered-cubic hollow site in an upright configuration. The individual NO molecule is imaged as a ring protrusion, which is characteristic of the doubly degenerate 2π(*) orbital. A triangular trimer is thermodynamically more favorable than the monomer and dimer, and its bonding structure was characterized by STM manipul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 56 publications
(66 reference statements)
6
34
0
Order By: Relevance
“…Our finding is consistent with previous theoretical studies 5,26,59−62 and STM observations by Shiotari and co-workers. 30 We confirmed that the conclusion is not changed when the slab thickness is increased (Table S1).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Our finding is consistent with previous theoretical studies 5,26,59−62 and STM observations by Shiotari and co-workers. 30 We confirmed that the conclusion is not changed when the slab thickness is increased (Table S1).…”
Section: Resultssupporting
confidence: 68%
“…The adsorption site of NO on Cu(111) was originally assigned to a 2-fold bridge site 13 and later it was assigned to a 3-fold hollow site. 17 Koshida et al revisited this system by EELS at 100 K and verified the formation of the NO trimer on Cu(111) that is observed by STM, 30 and the mode at 190 meV is reassigned to the N−O stretching modes of NO trimer rather than the NO monomer at the fcc-hollow site. 32 As will be discussed below, we found that the stretching modes are blue-shifted when NO absorbed in the trimer configuration, and those modes for the NO trimer agree well with the aforementioned experimental data.…”
Section: Resultsmentioning
confidence: 88%
“…Nitric oxide (NO) molecules on Cu surfaces have been prominent systems to monitor the local electronic states with STM images and STS measurements [35][36][37]. For an isolated NO molecule adsorbed onto Cu(110) at ∼15 K, the resonance state of its valence orbital (2π * ) remains at E F , and therefore, the orbital is visible in the STM image at low bias voltage [36].…”
Section: Introductionmentioning
confidence: 99%
“…22,35 (NO) 2 dimers have also been imaged on Cu(110) using scanning tunneling microscopy (STM), 33 and more recently, evidence for the formation (NO) 3 trimers on Cu(111) at 6 K has been collected with STM. 36 Nitric oxide also forms dimers on Pd(111) under certain conditions, as revealed by in situ infrared reflection absorption spectroscopy (IRAS). 37 Calculations performed on several different catalyst systems also support the intermediacy of an (NO) 2 dimer during nitric oxide reduction.…”
Section: Introductionmentioning
confidence: 99%